Equicontinuity of iterates of circle maps - Antonios Valaristos (International Journal of Mathematics and Mathematical Sciences)
Let f be a continuous map of the circle to itself. Necessary and sufficient conditions are given for the family ofiterates fnn=1∞ to be equicontinuous.